Protein kinase Cδ is essential for the IgG response against T-cell-independent type 2 antigens and commensal bacteria - Fukao, Saori; Haniuda, Kei; Tamaki, Hiromasa; Kitamura, Daisuke (eLife, 2021)
Antigens (Ags) with multivalent and repetitive structure elicit IgG production in a T-cell-independent manner. However, the mechanisms by which such T-cell-independent type-2 (TI-2) Ags induce IgG responses remain obscure. Here, we report that B-cell receptor (BCR) engagement with a TI-2 Ag but not with a T-cell-dependent (TD) Ag was able to induce the transcription of Aicda encoding activation-induced cytidine deaminase (AID) and efficient class switching to IgG3 upon costimulation with IL-1 or IFN-α in mouse B cells. TI-2 Ags strongly induced the phosphorylation of protein kinase C (PKC)δ and PKCδ mediated the Aicda transcription through the induction of BATF, the key transcriptional regulator of Aicda. In PKCδ-deficient mice, production of IgG was intact against TD Ag but abrogated against typical TI-2 Ags as well as commensal bacteria, and experimental disruption of the gut epithelial barrier resulted in fatal bacteremia. Thus, our results have revealed novel molecular requirements for class switching in the TI-2 response and highlighted its importance in homeostatic commensal-specific IgG production.
Keywords: immune response; B cells; TI-2; class switching